2010
DOI: 10.1177/0022034510381902
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease and Incident Diabetes

Abstract: Diabetes is associated with a high prevalence of periodontal disease, but little is known about the effects of periodontal disease on incident diabetes. In total, 5848 non-diabetic individuals aged 30-59 yrs who completed a health examination were analyzed in this study. They were divided into three categories: no pathological pockets, moderate periodontitis, or severe periodontitis. Incident diabetes was defined as newly diagnosed cases with fasting plasma glucose > 125 mg/dL. Cox proportional hazards models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 17 publications
5
109
2
3
Order By: Relevance
“…These SHIP data extended a previous cross-sectional report of elevated A1C levels among participants with periodontitis (20) as well as an earlier publication from NHANES I reporting increased levels of baseline periodontal disease to predict incident diabetes during two decades of follow-up (4). Although a recent study had equivocal findings for incident diabetes in a Japanese population (21), the mean follow-up time was only 6 years, which limited the number of incident cases and minimized power to detect the association observed. Collectively, these earlier studies were limited by an inability to address the potential role of insulin resistance as a mechanistic explanation of the aforementioned A1C change and incident diabetes findings.…”
Section: Discussionmentioning
confidence: 98%
“…These SHIP data extended a previous cross-sectional report of elevated A1C levels among participants with periodontitis (20) as well as an earlier publication from NHANES I reporting increased levels of baseline periodontal disease to predict incident diabetes during two decades of follow-up (4). Although a recent study had equivocal findings for incident diabetes in a Japanese population (21), the mean follow-up time was only 6 years, which limited the number of incident cases and minimized power to detect the association observed. Collectively, these earlier studies were limited by an inability to address the potential role of insulin resistance as a mechanistic explanation of the aforementioned A1C change and incident diabetes findings.…”
Section: Discussionmentioning
confidence: 98%
“…52 A long-term, largescaled follow-up study in Japan indicated no significant difference between periodontal treatment and the incidence of diabetes, but did suggest periodontitis as an increased risk for developing diabetes. 53 Taken together, of clinical relevance to us is that dentists should treat the periodontal condition in a patient's mouth and manage the patient's diabetic condition, in order to achieve optimal results after periodontal therapy. While good periodontal health might not necessarily be accompanied by a change in glycemic control, an improvement can potentially modify metabolic control, leading to an overall enhancement in the quality of life.…”
Section: Effects Of Periodontal Therapy On Periodontal Health and Glymentioning
confidence: 99%
“…Several studies support an association between periodontal disease and risk of chronic systemic conditions, including vascular disease, chronic obstructive pulmonary disease, diabetes mellitus, and cancer, including gastric adenocarcinoma. 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 These associations may be mediated by systemic inflammation, the immune response to periodontal infection, or direct invasion by pathogens. Previous studies of periodontal disease and risk of peptic ulcer have been limited by cross-sectional design, diagnoses that were not confirmed by medical record review, and a lack of information on key confounders, including smoking, aspirin and non-steroidal anti-inflammatory drug (NSAID) use, socioeconomic status, and Helicobacter pylori infection status.…”
Section: Introductionmentioning
confidence: 99%